The Indonesian Global Cocoa Chain’s Position in the Pandemic Era - Hasna Wijayati; Halifa Haqqi (International Journal on Social Science, Economics and Art, 2022)
In the GVC of cocoa commodities, Indonesia has a potential position as one of the suppliers of cocoa commodities. However, the cocoa industry sector is increasingly threatened when the world enters a crisis period due to the global pandemic in early 2020. For this reason, Indonesia has made many efforts to maintain its position in the GVC of cocoa commodities. This study attempts to analyze Indonesia's position in the global cocoa chain in the pandemic era. The method used is qualitative research with a library research approach. The theory used to analyze focuses on global value chain theory. This study finds that Indonesia's tried to maintain it’s position in global cocoa chain through economic stability, both at the domestic and global levels. This position is described in the aspect of increasing the contribution of cocoa commodities to GDP, increasing the export market share of Indonesian cocoa commodities in the global market, as well as increasing the competitiveness of the Indonesian economy. This condition becomes a parameter to measure the performance of Indonesia's political economy as well as demonstrates the capability of the Indonesian government in dealing with the global crisis due to the pandemic and minimizing the impact of the crisis on national stability. Thus, it can be concluded that Indonesia can still maintain its position in the global cocoa chain as an important supplier.